Tau Pathology Spread in PS19 Tau Transgenic Mice Following Locus Coeruleus (LC) Injections of Synthetic Tau Fibrils is Determined by the LC’s Afferent and Efferent Connections - Iba, Michiyo (Acta Neuropathol, 2015)
Filamentous tau inclusions are hallmarks of Alzheimer’s disease (AD) and other neurodegenerative tauopathies. An increasing number of studies implicate the cell-to-cell propagation of tau pathology in the progression of tauopathies. We recently showed [25] that inoculation of preformed synthetic tau fibrils (tau PFFs) into the hippocampus of young transgenic (Tg) mice (PS19) overexpressing human P301S mutant tau induced robust tau pathology in anatomically connected brain regions including the locus coeruleus (LC). Since Braak and colleagues hypothesized that the LC is the first brain structure to develop tau lesions and since LC has widespread connections throughout the CNS, LC neurons could be the critical initiators of the stereotypical spreading of tau pathology through connectome-dependent transmission of pathological tau in AD. Here, we report that injections of tau PFFs into the LC of PS19 mice induced propagation of tau pathology to major afferents and efferents of the LC. Notably, tau pathology propagated along LC efferent projections was localized not only to axon terminals but also to neuronal perikarya, suggesting transneuronal transfer of templated tau pathology to neurons receiving LC projections. Further, brainstem neurons giving rise to major LC afferents also developed perikaryal tau pathology. Surprisingly, while tangle bearing neurons degenerated in the LC ipsilateral to the injection site starting 6 months post-injection, no neuron loss was seen in the contralateral LC wherein tangle bearing neurons gradually cleared tau pathology by 6–12 months post-injection. However, the spreading pattern of tau pathology observed in our LC-injected mice is different from that in AD brains since hippocampus and entorhinal cortex, which are affected in early stages of AD, were largely spared of tau inclusions in our model. Thus, while our study tested critical aspects of the Braak hypothesis of tau pathology spread, this novel mouse model provides unique opportunities to elucidate mechanisms underlying the selective vulnerability of neurons to acquire tau pathology and succumb to or resist tau-mediated neurodegeneration.